KEPEMIMPINAN KEPALA SEKOLAH DALAM MENCIPTAKAN SEKOLAH EFEKTIF - Mardalena, Mardalena (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Effective schools show compatibility between the results achieved and those expected. In effective schools, all students not only students who have a high ability to learn, can develop themselves, but also students who have ordinary intellectual abilities can develop themselves as far as possible, especially when compared to the initial conditions when they just entered school. The principal is one of the important key factors in creating an effective school. Criteria that must be possessed by an effective principal: a) have a strong vision of the future of the school; b) have high expectations; c) ensure the learning runs effectively; d) efficient use of time and minimizing work stress and negative work conflicts; e) utilize and optimize various learning resources; f) utilizing information to direct learning planning; g) carry out continuous evaluation and improvement.